ANALYSIS OF THE VOLUME AND STRUCTURE OF HEALTH CARE SERVICES IN UKRAINE - Oksana Zghurska; Nataliya Struk; Yuriy Safonov; Anna Kulik; Olesia Romanenko (FinTechAlliance, 2022)
The purpose of this research article is to analyze the volume and structure of healthcare services in Ukraine in order to determine promising directions for the work of the national healthcare system, as well as to ensure the specified development parameters of the industry.To achieve this purpose, the research was conducted using the materials of the State Statistics Service of Ukraine and the data of the Ministry of Health to analyze the volume and structure of healthcare services in Ukraine in order to determine promising directions for the work of the national health care system, as well as to ensure the specified development parameters of the industry. The methodological basis of the research was made up of general and special methods, namely: system analysis with the aim of a comprehensive characterization of the strategic potential of the healthcare industry; statistical analysis (the standard deviation method) with the aim of analyzing the structure of healthcare facilities of Ukraine; the dynamics of the volume of sold products (goods, services) of business entities that provide services in health care and social protection; synthesis and comparison in diagnosing the state of the regional structure of private medicine in Ukraine and the dynamics of capital investment volumes of enterprises providing healthcare services.It has been established that at the current stage of the functioning of the healthcare market, the sources of funding for state medicine cannot fully provide the healthcare system with the necessary financial resources, introduce new methods of payment for health care and services, as well as improve the system of mandatory health insurance.Budget institutions should carry out marketing research, increase the level of comfort in the provision of healthcare services, increase the level of efficiency of the existing resource potential, especially human resources; develop, improve and diversify new types of services, and create decent conditions for organizing healthcare services.Paid healthcare services are characterized by the significant potential for growth, which is determined by the needs of the market and the population of the country. This segment of the economy is extremely promising in the direction of obtaining alternative opportunities for treatment and recovery in more comfortable conditions in accordance with the growing requirements for the quality of healthcare services and the availability of an individual approach to each patient.
АНАЛІЗ ОБСЯГУ ТА СТРУКТУРИ ПОСЛУГ ОХОРОНИ ЗДОРОВ’Я УКРАЇНИ
Keywords: healthcare services; health care system; private medicine; medical equipment; state healthcare services